Environment-friendly marbling EVA (Ethylene Vinyl Acetate) product based on multicolor injection molding and manufacturing process thereof

Through the multi-color injection molding process, combined with EVA substrate and fine fillers, the problems of complex processes, high costs, uneven texture and poor environmental protection in the process of realizing the marble texture effect of traditional EVA products are solved, and efficient and environmentally friendly marble EVA products are achieved.

CN119567488APending Publication Date: 2025-03-07DONGGUAN SHENGFA MICROPOROUS MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411770178.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The marble texture effect of traditional EVA products is complicated, the cost is high, the texture is uneven and the environmental protection is poor.

Method used

The environmentally friendly marble EVA product process based on multi-color injection molding is adopted, including the combination of EVA substrate, coloring material, fine particle filler and slow-release dissolved particles. Through the foaming in the injection machine and the temperature control of the mold partition, uniform marble texture effect is achieved.

Benefits of technology

It reduces production costs, improves production efficiency, achieves uniform and natural texture, improves visual effects, and has environmentally friendly performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119567488A_ABST
    Figure CN119567488A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer material processing, and discloses an environment-friendly marbling EVA (Ethylene Vinyl Acetate) product based on multicolor injection molding, which comprises the following components in percentage by weight: 85 to 95 percent of EVA base material, 0.3 to 0.7 percent of pigment, 3 to 5 percent of fine particle filler and 1 to 3 percent of slow-release dissolved particles, the invention further discloses a manufacturing process of the environment-friendly marbling EVA product based on multicolor injection molding. The manufacturing process comprises the following steps: S1, premixing raw materials: mixing the EVA base material, the pigment, the fine particle filler and the slow-release dissolved particles in proportion; s2, preheating of the injection machine and zoning temperature control: setting a temperature control system of the injection machine, keeping a main temperature zone at 80-90 DEG C, and setting a part of high temperature zones at 90-95 DEG C; through multi-color injection molding and accurate temperature control, the uniform and natural marble texture effect in the EVA product is realized, the process is simplified, the cost is reduced, and the environmental protection property is improved; the specific particle filler and the slow-release particles are adopted, so that the fineness and layering sense of the texture are improved, and the texture transition is more natural and smoother.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material processing, in particular to an environmentally friendly marble-grained EVA product based on multi-color injection molding and a manufacturing process thereof. Background Art

[0002] In the traditional EVA product processing, the common marble effect is usually achieved through spray painting or transfer printing technology. Although this method can present marble texture on the surface of the finished product, it has many defects. First of all, the spray painting and transfer printing processes add additional steps, resulting in cumbersome production processes and high production costs. In addition, these surface treatment technologies usually require the use of a large amount of chemical coatings and solvents, which not only affects the environmental performance of the product, but also causes quality problems such as paint peeling or fading during use, reducing the durability and aesthetics of the product.

[0003] In the prior art, some manufacturers try to achieve color or camouflage effects by directly mixing multi-color pigments into EVA materials and adopting multi-color injection molding. However, this type of process can only form dot-shaped or block-shaped texture effects, and it is difficult to obtain uniform, natural and smooth textures. In addition, there are deficiencies in texture levels and fineness, and it is impossible to completely simulate the texture effect of natural marble. In view of this, the present invention proposes an environmentally friendly marble-textured EVA product based on multi-color injection molding and a manufacturing process thereof. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides an environmentally friendly marble-textured EVA product based on multi-color injection molding and a production process thereof, which solves the problems of complex procedures, high costs, uneven texture and poor environmental performance in the process of achieving the marble texture effect of traditional EVA products.

[0005] To achieve the above objectives, the present invention is implemented through the following technical scheme: an environmentally friendly marble-grained EVA product based on multi-color injection molding, comprising the following components by weight percentage: 85% to 95% EVA substrate, 0.3% to 0.7% colorant, 3% to 5% fine particle filler and 1% to 3% slow-release soluble particles.

[0006] Preferably, the EVA substrate comprises EVA resin, a foaming agent, a cross-linking agent, a filler and a plasticizer.

[0007] Preferably, the fine particle filler is one of silicon dioxide, aluminum oxide or calcium carbonate particles.

[0008] Preferably, the slow-release dissolving particles are selected from calcium sulfate particles, calcium carbonate particles and calcium borate particles.

[0009] The process for manufacturing an environmentally friendly marble-grained EVA product based on multi-color injection molding is prepared by using the environmentally friendly marble-grained EVA product based on multi-color injection molding described above, and comprises the following steps:

[0010] S1. Raw material premixing: EVA substrate, colorant, fine particle filler and slow-release dissolving particles are mixed in proportion;

[0011] S2. Injection machine preheating and zone temperature control: Set the injection machine temperature control system, keep the main temperature zone at 80-90°C, and set some high temperature zones at 90-95°C;

[0012] S3, Foaming in the injection machine: Pour the prepared mixture into the injection machine, control the temperature of the material gun at 80-90°C, and the material completes the foaming process in the injection machine;

[0013] S4, temperature-controlled injection and mold forming: the foamed material is injected into the mold from the injection machine, and the mold is temperature-controlled in different zones to allow the material to flow and form in the mold;

[0014] S5. Demolding and quality inspection: Demold after cooling and check the product appearance and quality.

[0015] Preferably, the injection machine preheating and zone temperature control in step S2 specifically include the following steps:

[0016] S2.1, Injection machine temperature control system settings: the main temperature zone temperature is controlled at 80 ~ 90 ℃, the high temperature zone temperature is set at 90 ~ 95 ℃;

[0017] S2.2, Material preheating in sections:

[0018] Preliminary preheating: gradually put the mixed materials into the main temperature zone at 80-85℃ for preheating for 3-5 minutes;

[0019] Transition to high temperature zone: After the material reaches the initial preheating, it enters the high temperature zone at 90-95℃ and maintains for 5-10 minutes;

[0020] S2.3, Temperature control monitoring: Monitor the temperature of the injection molding machine in real time in different temperature zones, and keep the temperature difference within ±2°C.

[0021] Preferably, the temperature-controlled injection and mold forming in step S4 specifically include the following steps:

[0022] S4.1. Inject the foamed material into the mold: inject the foamed material from the injection machine at a medium speed of 200-300cm 3 / min injection into the mold, the middle plate is pulled out, and the temperature of the middle plate is controlled at 70-75℃;

[0023] S4.2, mold zone temperature control:

[0024] The upper mold temperature is set to 173-175°C;

[0025] The lower mold temperature is set to 176-180°C;

[0026] S4.3, mold pressure control: set the mold pressure to 5 ~ 10MPa;

[0027] S4.4. Segmented observation: Observe the flow state of the material in the mold every 1 minute after injection.

[0028] Preferably, the demoulding and quality inspection in step S5 specifically includes the following steps:

[0029] S5.1. Maintain mold temperature: After molding is completed, raise the mold temperature to 175-180°C and maintain this temperature for 1-3 minutes before opening the mold;

[0030] S5.2. Appearance inspection: After demoulding, carefully inspect the appearance of the product to ensure there are no obvious defects;

[0031] S5.3, Quality Inspection: Dimensional measurement and physical property testing of products to ensure compliance with predetermined quality standards and technical requirements.

[0032] The present invention provides an environmentally friendly marble-patterned EVA product based on multi-color injection molding and a manufacturing process thereof, which has the following beneficial effects:

[0033] 1. The present invention realizes uniform marble texture effect directly in the injection molding process through precise injection of several color materials and setting of gun temperature, avoiding the cumbersome process of realizing texture by spraying or transfer in the prior art, reducing costs, improving production efficiency, and being environmentally friendly.

[0034] 2. The present invention uses silica, alumina or calcium carbonate particles as fillers. Under the temperature control of the injection gun, the fine particles are evenly distributed, which improves the fineness of the texture. Compared with the traditional dot or block texture effect, the present invention makes the texture uniform and natural, avoiding the problem of uneven texture distribution in the existing process.

[0035] 3. The present invention generates tiny pores during the injection molding and cooling process by selecting calcium sulfate, calcium carbonate or calcium borate particles, thereby enriching the texture level, making the transition of the marble pattern more natural and smooth, and improving the visual effect, which is different from the single flatness of traditional coatings or transfer textures. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Flow chart of the process of the present invention. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Please see attached Figure 1 The embodiment of the present invention provides an environmentally friendly marble-grained EVA product based on multi-color injection molding, which includes the following components by weight percentage: 85% to 95% EVA substrate, 0.3% to 0.7% colorant, 3% to 5% fine particle filler and 1% to 3% slow-release dissolved particles.

[0039] The EVA matrix includes EVA resin, foaming agent, cross-linking agent, filler and plasticizer.

[0040] The fine particle filler can be any one of silica, alumina or calcium carbonate particles.

[0041] The sustained-release dissolving particles are selected from calcium sulfate particles, calcium carbonate particles and calcium borate particles.

[0042] The process for manufacturing an environmentally friendly marble-grained EVA product based on multi-color injection molding is adopted to prepare the environmentally friendly marble-grained EVA product based on multi-color injection molding, and comprises the following steps:

[0043] S1. Raw material premixing: EVA substrate, colorant, fine particle filler and slow-release dissolving particles are mixed in proportion;

[0044] S2. Injection machine preheating and zone temperature control: Set the injection machine temperature control system, keep the main temperature zone at 80-90°C, and set some high temperature zones at 90-95°C;

[0045] S3, Foaming in the injection machine: Pour the prepared mixture into the injection machine, control the temperature of the material gun at 80-90°C, and the material completes the foaming process in the injection machine;

[0046] S4, temperature-controlled injection and mold forming: the foamed material is injected into the mold from the injection machine, and the mold is temperature-controlled in different zones to allow the material to flow and form in the mold;

[0047] S5. Demolding and quality inspection: Demold after cooling and check the product appearance and quality.

[0048] S2 step injection machine preheating and zone temperature control specifically includes the following steps:

[0049] S2.1, Injection machine temperature control system settings: the main temperature zone temperature is controlled at 80 ~ 90 ℃, the high temperature zone temperature is set at 90 ~ 95 ℃;

[0050] S2.2, Material preheating in sections:

[0051] Preliminary preheating: gradually put the mixed materials into the main temperature zone at 80-85℃ for preheating for 3-5 minutes;

[0052] Transition to high temperature zone: After the material reaches the initial preheating, it enters the high temperature zone at 90-95℃ and maintains for 5-10 minutes;

[0053] S2.3, Temperature control monitoring: Monitor the temperature of the injection molding machine in real time in different temperature zones, and keep the temperature difference within ±2°C.

[0054] Step S4: temperature controlled injection and mold forming specifically include the following steps:

[0055] S4.1. Inject the foamed material into the mold: inject the foamed material from the injection machine at a medium speed of 200-300cm 3 / min injection into the mold, the middle plate is pulled out, and the temperature of the middle plate is controlled at 70-75℃;

[0056] S4.2, mold zone temperature control:

[0057] The upper mold temperature is set to 173-175°C;

[0058] The lower mold temperature is set to 176-180°C;

[0059] S4.3, mold pressure control: set the mold pressure to 5 ~ 10MPa;

[0060] S4.4. Segmented observation: Observe the flow state of the material in the mold every 1 minute after injection.

[0061] The demoulding and quality inspection in step S5 specifically include the following steps:

[0062] S5.1. Maintain mold temperature: After molding is completed, raise the mold temperature to 175-180°C and maintain this temperature for 1-3 minutes before opening the mold;

[0063] S5.2. Appearance inspection: After demoulding, carefully inspect the appearance of the product to ensure there are no obvious defects;

[0064] S5.3, Quality Inspection: Dimensional measurement and physical property testing of products to ensure compliance with predetermined quality standards and technical requirements.

[0065] Embodiment 1

[0066] Group distribution ratio:

[0067] EVA base material: 90%

[0068] Colorant: 0.5%

[0069] Fine particle filler (silicon dioxide): 4%

[0070] Sustained-release dissolving particles (calcium carbonate particles): 2%

[0071] Process steps:

[0072] S1: Weigh and mix the EVA substrate, colorant, silica particles and calcium carbonate particles according to a certain proportion.

[0073] S2:

[0074] S2.1: The main temperature zone is set to 85°C and the high temperature zone is set to 92°C.

[0075] S2.2: After preheating the material for 3 minutes, transfer to the high temperature zone and maintain it for 5 minutes.

[0076] S2.3: Monitor the temperature in real time and control the temperature difference within ±2℃.

[0077] S3: The gun temperature is controlled at 85°C and the foaming time is 6 minutes.

[0078] S4:

[0079] S4.1: Shot speed 250cm 3 / min, the middle plate temperature is 72°C.

[0080] S4.2: Upper mold temperature 174°C, lower mold temperature 177°C.

[0081] S4.3: The pressure inside the mold is 6MPa.

[0082] S4.4: Observe the material flow status every 1 minute.

[0083] S5:

[0084] S5.1. Maintain mold temperature: After molding is completed, raise the mold temperature to 177°C and maintain this temperature for 2 minutes before opening the mold;

[0085] S5.2. Appearance inspection: After demoulding, carefully inspect the appearance of the product to ensure there are no obvious defects;

[0086] S5.3, Quality Inspection: Dimensional measurement and physical property testing of products to ensure compliance with predetermined quality standards and technical requirements.

[0087] Summary: This embodiment realizes uniform multi-color injection molding and achieves an ideal marble effect through precise temperature control.

[0088] Embodiment 2

[0089] Component ratio (adjust the colorant content and filler type based on Example 1):

[0090] EVA base material: 88%

[0091] Colorant: 0.7%

[0092] Fine particle filler (select alumina): 3%

[0093] Sustained-release dissolving particles (calcium sulfate particles): 3%

[0094] Process steps:

[0095] S1: The EVA substrate, colorant, aluminum oxide particles, and calcium sulfate particles are weighed and mixed according to a certain proportion.

[0096] S2:

[0097] S2.1: The main temperature zone is set to 86°C and the high temperature zone is set to 93°C.

[0098] S2.2: After preheating the material for 4 minutes, transfer to the high temperature zone and maintain it for 6 minutes.

[0099] S2.3: The temperature difference is controlled within ±2℃.

[0100] S3: The gun temperature is controlled at 87°C and the foaming time is 7 minutes.

[0101] S4:

[0102] S4.1: Shot speed 275cm 3 / min, the middle plate temperature is 73℃.

[0103] S4.2: Upper mold temperature 175℃, lower mold temperature 178℃.

[0104] S4.3: The pressure inside the mold is 7 MPa.

[0105] S4.4: Observe the flow status every 1 minute.

[0106] S5:

[0107] S5.1. Maintain mold temperature: After molding is completed, raise the mold temperature to 175°C and maintain this temperature for 1.5 minutes before opening the mold;

[0108] S5.2. Appearance inspection: After demoulding, carefully inspect the appearance of the product to ensure there are no obvious defects;

[0109] S5.3, Quality Inspection: Dimensional measurement and physical property testing of products to ensure compliance with predetermined quality standards and technical requirements.

[0110] Summary: The contrast and layering of the texture are enhanced through higher pigment content and different fillers.

[0111] Embodiment 3

[0112] Component ratio (adjust the ratio of sustained-release particles to substrate based on Example 2):

[0113] EVA base material: 87%

[0114] Colorant: 0.5%

[0115] Fine particle filler (calcium carbonate): 4%

[0116] Sustained-release dissolving particles (calcium sulfate particles): 4%

[0117] Process steps:

[0118] S1: The EVA substrate, the colorant, the calcium carbonate particles and the calcium sulfate particles are weighed and mixed according to a certain proportion.

[0119] S2:

[0120] S2.1: The main temperature zone is set to 87°C and the high temperature zone is set to 94°C.

[0121] S2.2: After preheating the material for 5 minutes, transfer to the high temperature zone and maintain it for 8 minutes.

[0122] S2.3: The temperature difference is maintained at ±1.5℃.

[0123] S3: The gun temperature is controlled at 88°C and the foaming time is 8 minutes.

[0124] S4:

[0125] S4.1: Shot speed 285cm 3 / min, the middle plate temperature is 74°C.

[0126] S4.2: Upper mold temperature 176°C, lower mold temperature 179°C.

[0127] S4.3: The pressure inside the mold is 8MPa.

[0128] S4.4: Observe the flow status every 1 minute.

[0129] S5:

[0130] S5.1. Maintain mold temperature: After molding is completed, raise the mold temperature to 176°C and maintain this temperature for 2 minutes before opening the mold;

[0131] S5.2. Appearance inspection: After demoulding, carefully inspect the appearance of the product to ensure there are no obvious defects;

[0132] S5.3, Quality Inspection: Dimensional measurement and physical property testing of products to ensure compliance with predetermined quality standards and technical requirements.

[0133] Embodiment 4

[0134] Component ratio (filler and temperature control parameters are further adjusted based on Example 3):

[0135] EVA base material: 89%

[0136] Colorant: 0.3%

[0137] Fine particle filler (silicon dioxide): 3%

[0138] Sustained-release dissolving particles (calcium carbonate particles): 5%

[0139] Process steps:

[0140] S1: Weigh and mix the EVA substrate, colorant, silica particles and calcium carbonate particles according to a certain proportion.

[0141] S2:

[0142] S2.1: The main temperature zone is set to 88°C and the high temperature zone is set to 95°C.

[0143] S2.2: After preheating the material for 5 minutes, transfer to the high temperature zone and maintain it for 9 minutes.

[0144] S2.3: The temperature difference is maintained at ±1°C.

[0145] S3: The gun temperature is controlled at 89°C and the foaming time is 9 minutes.

[0146] S4:

[0147] S4.1: Shot speed 300cm 3 / min, the middle plate temperature is 75℃.

[0148] S4.2: Upper mold temperature 177℃, lower mold temperature 180℃.

[0149] S4.3: Pressure inside the mold 9MPa.

[0150] S4.4: Observe the flow status every 1 minute.

[0151] S5:

[0152] S5.1. Maintain mold temperature: After molding is completed, raise the mold temperature to 178°C and maintain this temperature for 2.5 minutes before opening the mold;

[0153] S5.2. Appearance inspection: After demoulding, carefully inspect the appearance of the product to ensure there are no obvious defects;

[0154] S5.3, Quality Inspection: Dimensional measurement and physical property testing of products to ensure compliance with predetermined quality standards and technical requirements.

[0155] Summary: Optimize the temperature control and filler combination to make the texture distribution more delicate and natural.

[0156] Embodiment 5

[0157] Component ratio (EVA substrate and colorant content are further adjusted based on Example 4):

[0158] EVA base material: 85%

[0159] Colorant: 0.7%

[0160] Fine particle filler (select alumina particles): 5%

[0161] Sustained-release dissolving particles (calcium sulfate particles): 3%

[0162] Process steps:

[0163] S1: The EVA substrate, colorant, aluminum oxide particles, and calcium sulfate particles are weighed and mixed according to a certain proportion.

[0164] S2:

[0165] S2.1: The main temperature zone is set to 89°C and the high temperature zone is set to 95°C.

[0166] S2.2: After preheating the material for 5 minutes, transfer to the high temperature zone and maintain it for 10 minutes.

[0167] S2.3: The temperature difference is maintained at ±1°C.

[0168] S3: The temperature of the material gun is controlled at 90°C and the foaming time is 10 minutes.

[0169] S4:

[0170] S4.1: Shot speed 300cm 3 / min, the middle plate temperature is 70℃.

[0171] S4.2: Upper mold temperature 175℃, lower mold temperature 178℃.

[0172] S4.3: The pressure inside the mold is 10MPa.

[0173] S4.4: Observe the flow status every 1 minute.

[0174] S5:

[0175] S5.1. Maintain mold temperature: After molding is completed, raise the mold temperature to 178°C and maintain this temperature for 2 minutes before opening the mold;

[0176] S5.2. Appearance inspection: After demoulding, carefully inspect the appearance of the product to ensure there are no obvious defects;

[0177] S5.3, Quality Inspection: Dimensional measurement and physical property testing of products to ensure compliance with predetermined quality standards and technical requirements.

[0178] Summary: The fineness and uniformity of the texture are further improved through a high proportion of fine fillers and optimized temperature control parameters.

[0179] Summary:

[0180] By gradually adjusting the ratio and temperature control parameters through Examples 1 to 5, the present invention optimizes the colorant ratio, filler type, and the selection of slow-release soluble particles, and accurately controls the temperature and pressure during the foaming and molding process, thereby achieving a stable and uniform multi-color marble effect, so that the product has good texture details and quality stability.

[0181] Demonstration experiment:

[0182] Purpose:

[0183] The present invention further verifies the significant advantages of improving texture uniformity, fineness, layer depth, environmental protection and cost efficiency through multi-color injection molding process. Compared with traditional painting or transfer process, a comprehensive evaluation of material performance and production efficiency is achieved.

[0184] Experimental design:

[0185] Experimental groups:

[0186] Experimental group (process of the present invention): marble-patterned EVA products were produced using the multi-color injection molding process with the parameters of Example 5.

[0187] Control group (traditional process): marble-patterned EVA products were made using traditional spray painting or transfer printing technology.

[0188] Experimental comparison indicators:

[0189] Texture uniformity: measured by color distribution, variance of particle distribution, surface roughness.

[0190] Texture depth and depth: Evaluate the thickness differences, depth and transition effects of textures.

[0191] Material properties: including flexibility, impact resistance and wear resistance.

[0192] Environmental performance: Volatile organic compound (VOC) emissions and waste generation.

[0193] Production cost and efficiency: production cost, energy consumption and production efficiency per unit of finished product.

[0194] Experimental steps:

[0195] Sample preparation:

[0196] Experimental group: marble-grained EVA product samples were prepared by multi-color injection molding process according to the component ratio and process parameters of Example 5.

[0197] Control group: basic products were prepared according to the same EVA substrate, and marble texture was formed by spray painting or transfer printing process.

[0198] Texture uniformity test:

[0199] Color density measurement: Select 20 random points on the sample and measure the color density value per unit area.

[0200] Particle distribution test: at 1cm 2 Within the region, count the number of particles in each sample and calculate the particle distribution variance.

[0201] Surface roughness: Use a surface profiler to measure the surface roughness values ​​Ra at different points and calculate the variance of the surface flatness.

[0202] Texture level and three-dimensional test:

[0203] Thickness difference measurement: The thickness difference is measured at 20 points on the sample surface, and the difference in thickness values ​​at different points reflects the texture layering.

[0204] Texture transition effect: Divide the texture transition area, measure the thickness difference of the transition area, and record its average transition naturalness.

[0205] Material performance test:

[0206] Flexibility: The maximum bending angle and bending strength of the sample are measured through a 3-point bending test.

[0207] Impact resistance: The impact resistance of the sample was measured using an impact test device.

[0208] Wear resistance: The weight loss of the sample under the same wear conditions was measured using an abrasion testing machine to calculate the wear resistance.

[0209] Environmental testing

[0210] VOC emissions: Use gas chromatography to test the VOC emissions of the sample within 24 hours.

[0211] Waste quantity: record the waste generated in each batch of production (including paint residue, transfer film, etc.) and calculate the waste quantity per unit production.

[0212] Production cost and efficiency calculation:

[0213] Production cost: record the cost of materials, energy consumption and processes for the experimental group and the control group, and calculate the unit cost of each batch of samples.

[0214] Energy consumption measurement: measure the energy consumption per unit time and calculate the energy consumption per unit product.

[0215] Production efficiency: Under the same production conditions, record the number of finished products per hour.

[0216] Experimental results summary table:

[0217] Compare Projects Experimental group (process of the present invention) Control group (traditional technology) Color density variance 0.018 0.12 Particle distribution variance 0.03 0.17 Surface roughness Ra variance 0.04 0.21 Thickness difference (μm) 120~140 60~90 Thickness difference in texture transition area (μm) 15 30 Flexibility (maximum bending angle °) 75 60 Impact strength(MPa) 12 8 Wear resistance (wear loss mg) 1.2 3.5 <![CDATA[VOC emissions (mg / m 3 )]]> 5 50 Waste volume (g / batch) 2 35 Production cost (yuan / batch) 80 100 Energy consumption per unit product (kWh / unit) 0.3 0.6 Production efficiency (pieces / hour) 150 100

[0218] Experimental summary:

[0219] Texture uniformity: The variance of the experimental group in color density, particle distribution, and surface roughness was significantly smaller than that of the control group, indicating that the present invention achieves the control effect of uniform texture distribution through multi-color injection molding and precise temperature control, avoiding the problem of uneven texture caused by traditional spray painting or transfer.

[0220] Texture hierarchy and three-dimensional effect: The experimental group showed higher texture hierarchy depth and natural transition in thickness difference and thickness difference in texture transition area, showing the advantages of the marble pattern of the present invention in visual hierarchy and three-dimensional effect.

[0221] Material properties: The flexibility, impact resistance and wear resistance of the experimental group are better than those of the control group, indicating that the present invention optimizes the physical properties of the product through reasonable material ratio and precise process control, making it more suitable for practical application requirements.

[0222] Environmental protection: The VOC emission of the experimental group is 5mg / m 3 , significantly lower than the control group of 50mg / m 3 The waste volume is only 2g / batch, which is much lower than 35g / batch of the control group. The process of the present invention does not require painting and transfer treatment, reduces pollution emissions, and shows environmental advantages.

[0223] Production cost and efficiency: The unit cost of the experimental group was 20% lower than that of the control group, and the production efficiency was increased by 50%, indicating that the multi-color injection molding process of the present invention is significantly superior to the traditional process in reducing costs and improving production efficiency.

[0224] Summary: This experiment fully verified the technical advantages of the present invention through quantitative tests of multiple indicators. The present invention is significantly superior to traditional spray painting and transfer processes in terms of texture uniformity, layering, material performance, environmental protection and production efficiency, proving the innovation and practicality of the technical solution of the present invention, and is suitable for promotion and application in the production of efficient and environmentally friendly marble EVA products.

[0225] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Environmentally friendly marble-grained EVA products based on multi-color injection molding, characterized in that: The invention comprises the following components by weight percentage: 85% to 95% of EVA base material, 0.3% to 0.7% of colorant, 3% to 5% of fine particle filler and 1% to 3% of slow-release dissolving particles.

2. The environmentally friendly marble-grained EVA product based on multi-color injection molding according to claim 1, characterized in that: The EVA substrate comprises EVA resin, a foaming agent, a cross-linking agent, a filler and a plasticizer.

3. The environmentally friendly marble-grained EVA product based on multi-color injection molding according to claim 1, characterized in that: The fine particle filler is optionally one of silicon dioxide, aluminum oxide or calcium carbonate particles.

4. The environmentally friendly marble-grained EVA product based on multi-color injection molding according to claim 1, characterized in that: The sustained-release dissolving particles are selected from calcium sulfate particles, calcium carbonate particles and calcium borate particles.

5. The process for producing environmentally friendly marble-grained EVA products based on multi-color injection molding is characterized in that: The preparation of the environmentally friendly marble-grained EVA product based on multi-color injection molding according to any one of claims 1 to 4 comprises the following steps: S1. Raw material premixing: EVA substrate, colorant, fine particle filler and slow-release dissolving particles are mixed in proportion; S2. Injection machine preheating and zone temperature control: Set the injection machine temperature control system, keep the main temperature zone at 80-90°C, and set some high temperature zones at 90-95°C; S3, Foaming in the injection machine: Pour the prepared mixture into the injection machine, control the temperature of the material gun at 80-90°C, and the material completes the foaming process in the injection machine; S4, temperature-controlled injection and mold forming: the foamed material is injected into the mold from the injection machine, and the mold is temperature-controlled in different zones to allow the material to flow and form in the mold; S5. Demoulding and quality inspection: Demould after a period of time and check the product appearance and quality.

6. The process for producing an environmentally friendly marble-grained EVA product based on multi-color injection molding according to claim 5, characterized in that: The S2 step of preheating the injection machine and controlling the temperature of each zone specifically includes the following steps: S2.1, Injection machine temperature control system settings: the main temperature zone temperature is controlled at 80 ~ 90 ℃, the high temperature zone temperature is set at 90 ~ 95 ℃; S2.2, Material preheating in sections: Preliminary preheating: gradually put the mixed materials into the main temperature zone at 80-85℃ for preheating for 3-5 minutes; Transition to high temperature zone: After the material reaches the initial preheating, it enters the high temperature zone at 90-95℃ and maintains for 5-10 minutes; S2.3, Temperature control monitoring: Monitor the temperature of the injection molding machine in real time in different temperature zones, and keep the temperature difference within ±2°C.

7. The process for producing an environmentally friendly marble-grained EVA product based on multi-color injection molding according to claim 5, characterized in that: The temperature-controlled injection and mold forming in step S4 specifically include the following steps: S4.

1. Inject the foamed material into the mold: inject the foamed material from the injection machine at a medium speed of 200-300cm 3 / min injection into the mold, the middle plate is pulled out, and the temperature of the middle plate is controlled at 70-75℃; S4.2, mold zone temperature control: The upper mold temperature is set to 173-175°C; The lower mold temperature is set to 176-180°C; S4.3, mold pressure control: set the mold pressure to 5 ~ 10MPa; S4.

4. Segmented observation: Observe the flow state of the material in the mold every 1 minute after injection.

8. The process for producing an environmentally friendly marble-grained EVA product based on multi-color injection molding according to claim 5, characterized in that: The demoulding and quality inspection in step S5 specifically includes the following steps: S5.

1. Maintain mold temperature: After molding is completed, raise the mold temperature to 175-180°C and maintain this temperature for 1-3 minutes before opening the mold; S5.

2. Appearance inspection: After demoulding, carefully inspect the appearance of the product to ensure there are no obvious defects; S5.3, Quality Inspection: Dimensional measurement and physical property testing of products to ensure compliance with predetermined quality standards and technical requirements.